Positive and negative phenotyping of increasing Zn concentrations by Biospeckle Optical Coherence Tomography in speedy monitoring on lentil (Lens culinaris) seed germination and seedling growth - Y. Sanath K. De Silva (Elsevier, 2021)
Reliable seed screening that can speedily detect qualities such as dormancy and seed germination can be of great significance in improving plant growth, crop yield, and quality. On the other hand, Optical Coherent Tomography (OCT) has been extensively used as a potential tool in visualizing structures of biological objects, especially the retina. However, its role in visualizing temporal changes that accompany these structures as speckle noise remains relatively underexplored. The present study of biospeckle OCT or bOCT demonstrates the potential of speckles in plant physiological studies. In this paper, the potential of bOCT in speedily investigating the positive and negative phenotyping of increasing Zn concentrations on lentil seed (Lens culinaris) germination and seedling growth were demonstrated. Lentil seeds were exposed to three different Zn concentrations of 0 (control), 5, 10, and 100 mg/L for 24 h, and the structural OCT images were acquired to calculate the temporal fluctuations in the image as a quantity called the average speckle contrast (γ). The average speckle contrast was calculated after 6 h, 12 h, and 24 h of exposure to different concentrations. Statistically significant differences were observed even within 12 h of exposure under all the Zn treatments compared to control. In comparison, the conventional measurements of germination rate, root and shoot lengths, and fresh and dry weights of seedlings took nearly 48 h to observe significant changes. Furthermore, the Zn uptake measurements were significant for all the tested concentrations after seven days of exposure. Further, bOCT results showed a clear concentration dependent effect with 5, 10 mg/L producing positive effects, while a high concentration of 100 mg/L showing a detrimental effect on seed germination and seedling growth. Thus, the current study results imply that bOCT can be used to investigate the positive and negative effects of increasing Zn concentrations on seed germination and seedling growth at an early stage before germination.